A CASE STUDY ON THE USE OF GRAMMARLY TO ENHANCE WRITING ACCURACY AMONG FOURTH SEMESTER STUDENTS OF THE ENGLISH LEARNING PROGRAM AT UIN MADURA - Handayani, Rini; Habibullah, Mosleh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the use of Grammarly in supporting writing accuracy among fourth-semester students of the English Learning Program at UIN Madura. This research employed a qualitative case study design involving nine students. Data were collected through observation, interviews, and documentation. The findings revealed that Grammarly helped students improve grammar, punctuation, spelling, and sentence structure. In addition, students showed positive perceptions toward Grammarly because it was easy to use and assisted them in revising their writing. However, some students tended to depend on the application without fully understanding the corrections. Therefore, Grammarly can be used as a supportive tool to enhance students’ writing accuracy. Keywords: Grammarly, writing accuracy, writing skill, EFL students